A structured medication review tool to promote psychotropic medication optimisation for adults with intellectual disability: feasibility study - Angela Hassiotis; Rory Sheehan; Louise Marston; Nicola Morant; André Strydom; Federico Fiori; Paramala Santosh (BMJ Open)
Objectives To investigate the feasibility of delivering structured psychotropic medication review in community services for adults with intellectual disability (ID).Design Single-arm feasibility study conducted over a 6-month period.Setting Specialist community ID teams in England.Participants Psychiatrists working with adults with ID and adults with ID who had been prescribed psychotropic medication.Intervention A structured web-based psychotropic medication review tool (the HealthTracker-based structured medication review) comprising measures of therapeutic benefit and adverse side-effects was made available for use by psychiatrists in routine clinic appointments. A summary measure of medication effectiveness was graphically presented to aid discussion and decision-making.Main outcome measures Feasibility metrics including number of people with ID referred, eligible and recruited, and uptake of the medication review tool in naturalistic clinical settings. Psychiatrist and patient feedback was collected to assess acceptability of the intervention and suggestions for development.Results Fifteen psychiatrists from five clinical teams took part. In total 94 potentially eligible people with ID were referred, of whom 79 (84%) were recruited and together underwent 97 medication reviews over the 6-month study period. Feedback from participants with ID was favourable. Psychiatrists indicated that the HealthTracker-based structured medication review was broadly acceptable and suggested adaptations to improve integration with existing information technology systems and to enhance patient involvement in the review.Conclusions Structured psychotropic medication review can be used in community services for adults with ID as part of a programme of medication optimisation. It would be feasible to test clinical and patient outcomes of the HealthTracker-based medication review in a randomised clinical trial.